Should Transit Continue to Chase Development?: Scenario Modeling and Analysis Supporting Regional Efficiency and Cost-Effectiveness in Washington, D.C., Region. Issue 1 (2016) - Davis, Allison; Leven, Dalia
The Washington Metropolitan Area Transit Authority (WMATA) operates Metrorail, Metrobus, and MetroAccess paratransit services in the Washington, D.C., region. By 2040, the region's forecast projects an increase in population and jobs in the transit zone by 22% and 34%, respectively, and an increase in the remainder of the region by 36% and 46%, respectively. Much of that growth is planned where transit is already crowded, whereas many other areas that have high-quality transit continue to be underdeveloped. The result is an unbalanced use of the transit system. To handle the forecast growth, transit infrastructure could be built at high cost, but what if land use and other policies were applied regionally to make better use of the transit system and perhaps postpone the need for expansion? Scenarios modeled by WMATA and its consultants are summarized. The study developed and tested six policy scenarios for 2040 that would keep transit constant while varying land use and other policies. The results show that some real benefits could accrue to the Washington region if decisions about land use, pricing, and other policies were to be made within a regional context rather than the existing parochial approach that seeks to maximize jurisdictional benefits alone. Capacity improvements to the transit network would also be needed to address forecast transit crowding and Metrorail core capacity limitations. However, making changes to land use decisions while adding pricing strategies could provide the region with the necessary funds to make expansion possible.